Characterization of Solid Renal Masses using 64-Slice Multidetector CT Scanner - Saleh S. El-Esawy; Mohamed E. Abou El-Ghar; Ghada M. Gaballa; Saly A. Zahra (The Scientific World Journal)
The purpose of our study was to assess the role of a 64-slice multidetector CT (MDCT) scanner in the characterization of different solid renal masses, using a simplified approach to correct the postenhancement attenuation values. The study included 96 consecutive adults (58 men, 38 women) with renal masses; 93 with unilateral and three with bilateral masses. All of our patients underwent multiphasic CT study including pre- and postcontrast corticomedullary (CM) and nephrographic phases. We analyzed the images and corrected the postcontrast attenuation values at the CM phase. The postbiopsy or -surgical data were used as reference standard. There were 53 masses at the right kidney, 40 at the left kidney, and three bilateral. The final diagnosis of the 96 solid parenchymal masses were 28 clear-type renal cell carcinoma (RCC), 22 papillary-type RCC, 21 chromophobe-type RCC, six XP 11.2 chromosomal translocation–type RCC, 15 angiomyolipoma (AML), and seven oncocytoma. All the AML had fat, with attenuation values less than -40 HU at the nonenhanced scan. There is no difference in the precontrast attenuation values for the different types other than AML. At the postcontrast CM phase after the correction of the attenuation values, the clear cell type could be separated easily, with attenuation values >20 with specificity, sensitivity, and overall accuracy of 92, 84, and 93%, respectively. The 64-slice MDCT scanner with application of enhancement values correction allows diagnosis of clear cell carcinoma. Also, AML could be identified easily with fat inside at the precontrast scan.